THE REGENERATION POTENTIAL OF BALAM (Palaquium burchii H.J.L) IN THE ARBORETUM OF UNIVERSITY OF RIAU - Khairilkasdi; Evi Sribudiani; M. Mardhiansyah (Jurnal Ilmu Ilmu Kehutanan, 2017)
Arboretum as a conservation area that aims to maintain the tree species and ecological benefits of having a variety of plants or trees that have high economic value. One of the plants or trees that have high economic value is balam (Palaqium burchii HJL). The Natural regeneration in a forest area has a very important role to sustain the kind of quantity and quality of balam in the future. Balam (Palaqium burchii HJL) entered in the family Saportaceae. Balam (Palaquium burchii HJL) is a native plant of Indonesia that spread throughout in mainland Indonesia and found most widely in the areas of Borneo. Wood types of balam (Palaqium burchii HJL) has class IV in durability and class II in powers. This study was conducted in Arboretum of University of Riau. Bina Widya Street KM12,5 Panam, District Tampan, Pekanbaru, Riau Province. Arboretum has an area of ± 10 Ha. The research was conducted in March until June 2015. Based on the results of the study showed that the entire swath of the observations which the regeneration of balam only 1.07%, it can be stated that the regeneration of balam in Arboretum area of University of Riau is still relatively low.